1996
DOI: 10.1029/96jd01090
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐based measurements of NOx and total reactive oxidized nitrogen (NOy) at Sable Island, Nova Scotia, during the NARE 1993 summer intensive

Abstract: Measurements of NO, NO2, and total reactive oxidized nitrogen (NOy) were added to ongoing measurements of aerosols, CO, and O3 at Sable Island (43°55′N, 60°01′W), Nova Scotia, during the North Atlantic Regional Experiment (NARE) 1993 summer intensive. Ambient levels of NOx and NOy were found to be highly variable, and elevated levels can be attributed to the transport of polluted continental air or presumably to relatively fresh emissions from sources upwind (e.g., ship traffic). The median values for NOx and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 45 publications
4
12
0
Order By: Relevance
“…In comparison to THF, the reduced linearity between O 3 and CO at CAS appeared to be related to the absence of a high end in the O 3 distribution (>80 ppbv). The O 3 -CO relationship and the value of its associated slope are sensitive to the end member distributions of CO and O 3 [Wang et al, 1996;Parrish et al, 1998]. The value of the slopes observed at the AIRMAP sites are in agreement with previous studies in the northeastern United States exhibiting a range of 0.21-0.41 [Parrish et al, 1993;Chin et al, 1994;Buhr et al, 1996].…”
Section: Key Characteristics Of the O 3 -Co Relationshipsupporting
confidence: 88%
See 1 more Smart Citation
“…In comparison to THF, the reduced linearity between O 3 and CO at CAS appeared to be related to the absence of a high end in the O 3 distribution (>80 ppbv). The O 3 -CO relationship and the value of its associated slope are sensitive to the end member distributions of CO and O 3 [Wang et al, 1996;Parrish et al, 1998]. The value of the slopes observed at the AIRMAP sites are in agreement with previous studies in the northeastern United States exhibiting a range of 0.21-0.41 [Parrish et al, 1993;Chin et al, 1994;Buhr et al, 1996].…”
Section: Key Characteristics Of the O 3 -Co Relationshipsupporting
confidence: 88%
“… Cooper et al [2001] suggested that in the upper Great Lakes region of the United States, frequent transitions between air masses of contrasting source regions with differing O 3 ‐CO characteristics can collectively play an important role in forming the O 3 ‐CO linear relationship with a slope of 0.3. Additional studies pointed out that the O 3 ‐CO relationship and slope are sensitive to the upper end values of the CO and O 3 distributions [ Wang et al , 1996; Parrish et al , 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Parrish et al [1998] noted that the O3/CO relationship is sensitive to the end members of a distribution, being driven by extremely clean (e.g., hurricane events) and extremely polluted events over the North Atlantic Ocean. Similar conclusions were drawn by Carroll et al [1994] and Wang et al [1996] for data collected at Sable Island in the western North Atlantic Oceanß Moody et al [1998] found that the O3/CO slope measured at Harvard Forest varied according to air mass transport path. This manuscript builds upon these findings and further explores the influence of air mass origin on the O3/CO slope.…”
Section: Trace-gas Mixing Ratios By Air Mass Originsupporting
confidence: 81%
“…This is a useful diagnostic for giving a general indication of the potential for O 3 formation but it should be noted that calculating OPE in this way represents an upper limit due to potential loss of O x and NO y species from the plume air due to wet and dry deposition (e.g. Wang et al, 1996;Rickard et al, 2002). For relatively fresh biomass burning plumes measured on flight B626 the slope of the fit is 1.6 ± 15.6 ppbv ppbv −1 relative to AN and 0.07 ± 13.5 ppbv ppbv −1 relative to NO z (i.e., 1.6 O x molecules are produced relative to each molecule of AN and 0.07 O x molecules per molecule of NO z ).…”
Section: Ozone Production Efficiencymentioning
confidence: 99%